Republic of Croatia : Financial Sector Assessment Update - World Bank (Washington, DC, 2012)
This Financial Sector Assessment (FSA) summarizes the structural and developmental aspects of the 2007 Financial Sector Assessment Program (FSAP) update report for the Republic of Croatia. An in-depth elaboration on the stability and prudential oversight aspects of the FSAP Update, including factual updates of core principles and Report on the Observance of Standards and Codes (ROSCs), are summarized in the Financial System Stability Assessment (FSSA) that was discussed by the International Monetary Fund (IMF) Board as part of the Article IV consultation, in May 2008. This FSA should be read together with the Fund's FSSA in order to obtain a full sense of the findings and recommendations of the 2007 Croatia FSAP Update. The main conclusion of the FSAP update is that, although substantial improvements in regulation, supervision and institutional capacity are observed, challenges remain given the rapidly growing credit and securities market sectors.